Conductive stable coating for metal bipolar plate and preparation method thereof
By preparing nanoparticle pyrrole coating and hybrid material dispersion on metal bipolar plates and electrophoretic deposition combined with epoxy resin, the corrosion and passivation of metal bipolar plates in acidic environments is solved, good corrosion resistance and conductivity are achieved, and the service life of bipolar plates is extended.
Patent Information
- Application Number
- CN202410445032.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-15
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-04-15
AI Technical Summary
Metal bipolar plates are prone to corrosion and passivation in acidic PEMFC environments, resulting in an increase in electron transmission resistance and shortening the service life of bipolar plates.
A three-electrode system was used to perform electrical polymerization under constant current conditions to prepare a nanoparticle pyrrole coating, and ultrasonic dispersion of Ti3C2Tx and intercalated layered double hydroxides were dispersed to form a hybrid material dispersion liquid, and electrophoreically deposited with epoxy resin to obtain a conductive stable coating for metal bipolar plates.
It improves the corrosion resistance and conductivity of metal bipolar plates, extends the service life of bipolar plates, and meets the corrosion resistance requirements of the US Department of Energy standards.
Smart Images

Figure CN118073593B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a conductive stable coating for a metal bipolar plate and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) can convert hydrogen energy into electrical energy, and are characterized by high efficiency, cleanliness, and low operating temperature. Although PEMFCs are widely regarded as a renewable green energy system, their commercialization is limited by their lifespan and cost. Bipolar plates are an important component of PEMFCs, accounting for more than 45% of the entire cost and weight. They are mainly used to collect current, prevent gas leakage, and separate the anode and cathode regions. Traditional graphite bipolar plates have good corrosion resistance and conductivity, but they are brittle, have high manufacturing costs, and have poor air tightness, making them difficult to apply on a large scale. On the other hand, metal bipolar plates have attracted the interest of many people due to their superior air tightness, high mechanical strength, and low cost. However, metal bipolar plates are easily corroded and passivated in the acidic PEMFC environment, resulting in increased electron transfer resistance and shortened bipolar plate service life.
[0003] Therefore, there is a need for a bipolar plate that has good service life under acidic conditions and has good electrical conductivity. Summary of the invention
[0004] The object of the present invention is to provide a conductive stable coating for a metal bipolar plate, so as to solve the technical problem of poor corrosion resistance of the metal bipolar plate in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a conductive stable coating for a metal bipolar plate, comprising the following steps:
[0007] Step (1) cleaning the surface of the substrate to remove oil stains and oxide film on the surface;
[0008] Step (2) electropolymerizing in an electrolyte mixture using a three-electrode system under constant current conditions, and drying to obtain a nanoparticle pyrrole coated bipolar plate;
[0009] In the above process, polypyrrole uses TiN as a nucleation site and wraps around the surface of TiN, and a composite coating of modified TiN nanoparticles and polypyrrole is deposited on the substrate by electrochemical polymerization in a phytic acid electrolyte.
[0010] Step (3) ultrasonically dispersing Ti3C2Tx and intercalated layered double hydroxide in water respectively to obtain a Ti3C2Tx dispersion and an intercalated layered double hydroxide dispersion, then adding the Ti3C2Tx dispersion to the intercalated layered double hydroxide dispersion, and after ultrasonic treatment, obtaining a hybrid material dispersion;
[0011] In the above process, intercalated layered double hydroxides were assembled on the Ti3C2Tx surface through electrostatic interaction.
[0012] Step (4) adding the diluted epoxy resin into the activated water, stirring and then standing to obtain the activated epoxy resin;
[0013] Step (5) adds the hybrid material dispersion prepared in step (3) to the activated epoxy resin prepared in step (4), and after stirring, applies voltage between the cathode nanoparticle pyrrole coated bipolar plate and the anode graphite plate to complete the electrophoretic deposition process, and bakes to obtain a conductive stable coating for the metal bipolar plate.
[0014] Preferably, the substrate in step (1) is a steel bipolar plate for a fuel cell.
[0015] More preferably, the steel is stainless steel.
[0016] Preferably, in step (2), the current density of the constant current is 1 mA·cm -2 ; The electropolymerization time is 20-30min; Drying conditions: The drying temperature is room temperature, and the drying time is 8-16h; The three-electrode system consists of a substrate as a working electrode, Ag / AgCl (sat.KCl) as a reference electrode, and a Pt sheet as a counter electrode.
[0017] Preferably, in step (2), the method for preparing the electrolyte mixture comprises the following steps:
[0018] 0.1-0.2 g of TiN nanoparticles and 0.14-0.28 g of camphorsulfonic acid are added to 1-2 L of water, and after ultrasonic treatment for 20-40 min, nitrogen is passed for 20-40 min, and then 7.9-16 g of pyrrole and 6.6-13.1 g of phytic acid are added to obtain an electrolyte mixture.
[0019] In the above process, the high surface energy of camphorsulfonic acid is used to functionalize the original TiN nanoparticles that are easy to agglomerate, thereby obtaining a negatively charged surface and improving the dispersion stability.
[0020] Preferably, in step (3), the dosage ratio of Ti3C2Tx, layered double hydroxide and water is (0.015-0.03) g:(0.045-0.09) g:(100-200) mL; and the ultrasonic treatment time is 20-40 min.
[0021] Preferably, in step (3), the method for preparing the intercalated layered double hydroxide comprises the following steps:
[0022] 6.1-12.2 g of MgCl2·6H2O and 5.6-11.2 g of Al(NO3)3·9H2O are dissolved in 100-200 mL of water to obtain a mixed solution A, and then 7.3-15 g of Na2MoO4·2H2O and 5.4-10.8 g of urea are dissolved in 100-200 mL of water to obtain a mixed solution B. The mixed solution A and the mixed solution B are mixed, and the pH is adjusted to 9-10 with a 1 mol / L NaOH solution, and then stirred at 80-100° C. for 4-6 h in a nitrogen atmosphere, reacted in a hydrothermal reactor at 110-130° C. for 24-48 h, filtered, and the filter residue is washed with deionized water 3-5 times, and freeze-dried to obtain an intercalated layered double hydroxide.
[0023] In the above process, molybdate (MoO4 2- )Intercalated magnesium aluminum layered double hydroxide.
[0024] Preferably, in step (4), the active water is obtained by adding 2-4 g of glacial acetic acid to 100-200 mL of water and stirring for 10-20 min; the diluted epoxy resin is obtained by adding 60-120 g of epoxy resin to 100-200 mL of water and stirring for 20-40 min; the stirring treatment time is 0.5-1.5 h; and the standing time is 12-36 h.
[0025] Preferably, in step (5), the stirring treatment conditions are: the stirring treatment time is 0.5-1.5h, and the stirring treatment speed is 400-600rpm; the voltage application method is: applying 140-160V DC voltage for 1-3min; the baking conditions are: the baking temperature is 160-180°C, and the baking time is 15-25min.
[0026] The conductive stable coating for metal bipolar plates is prepared by the method for preparing the conductive stable coating for metal bipolar plates.
[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0028] 1. In the present invention, a large amount of hydroxyl and amino groups are adsorbed on the surface of the TiN nanopowder, which has excellent chemical stability and superior electrical conductivity. TiN is modified with camphorsulfonic acid, and then a dense nanoparticle pyrrole coating with less pores and defects is formed by the electrostatic interaction between the modified TiN and polypyrrole; the doping of TiN leads to an increase in the surface roughness of the coating, increases the hydrophobicity of the coating, and TiN makes the transmission path of the corrosive medium through the coating more complicated and circuitous, while the hydrogen bond between the counter ion camphorsulfonic acid and TiN and the hydrophobicity of the composite coating make it difficult for the corrosive ions to exchange with the counter ions, thereby improving the corrosion resistance; TiN acts as a "conductive bridge" of the polypyrrole, thereby improving the electrical conductivity of the coating.
[0029] 2. The Ti3C2Tx in the present invention has excellent electrical conductivity, and can block the corrosive medium and extend the corrosion path, thereby improving the corrosion resistance. The isolation of the nanoparticle pyrrole coating avoids the galvanic corrosion of the substrate after the hybrid material coating is damaged. At the same time, the barrier effect of the hybrid material coating is also conducive to preventing the damage of the inner nanoparticle pyrrole coating. The double-layer coating has both anodic protection and enhanced barrier effect, thereby preventing the single-layer conductive polymer coating from being damaged by corrosive media such as Cl- during long-term immersion, resulting in pore defects. The coordinated cooperation of the inner and outer coatings has good corrosion resistance. The hybrid material coating has active corrosion inhibition ability. In the sodium chloride solution, the molybdate corrosion inhibitor layer between magnesium and magnesium is released and deposited on the surface to form a corrosion inhibition film, MoO4 2- With Cl - The ion exchange interaction between the two causes the hybrid material coating to absorb chloride ions and release the corrosion inhibitor MoO4 2- , the released MoO4 2- A corrosion-inhibiting film is formed to prevent further corrosion, so the conductive stable coating for metal bipolar plates prepared by the present invention has good stability, corrosion resistance and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 It is a process flow chart of preparing the conductive stable coating for metal bipolar plates of the present invention;
[0032] Figure 2 is a histogram of corrosion current of the conductive stable coating of the present invention;
[0033] Figure 3is a bar graph of the contact resistance of the conductive stabilizing coating of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0035] This embodiment discloses a method for preparing an electrolyte mixture, comprising the following steps:
[0036] 0.15 g of TiN nanoparticles and 0.21 g of camphorsulfonic acid were added to 1.5 L of water, and after ultrasonic treatment for 30 min, nitrogen was passed through the water for 30 min, and then 12 g of pyrrole and 9.9 g of phytic acid were added to obtain an electrolyte mixture. Example 2
[0037] This embodiment discloses a method for preparing an intercalated layered double hydroxide, comprising the following steps:
[0038] 9.1 g MgCl2·6H2O and 8.4 g Al(NO3)3·9H2O were dissolved in 150 mL water to obtain a mixed solution A, and then 10.2 g Na2MoO4·2H2O and 8.1 g urea were dissolved in 150 mL water to obtain a mixed solution B. The mixed solution A and the mixed solution B were mixed, and the pH was adjusted to 9.5 with a 1 mol / L NaOH solution. Then, the mixture was stirred at 90°C for 5 h in a nitrogen atmosphere, and then reacted in a hydrothermal reactor at 120°C for 36 h. The mixture was filtered, and the filter residue was washed 4 times with deionized water. After freeze-drying, an intercalated layered double hydroxide was obtained. Example 3
[0039] See also Figure 1 As shown, this embodiment discloses a method for preparing a conductive stable coating for a metal bipolar plate, comprising the following steps:
[0040] Step (1) cleaning the surface of the substrate to remove oil stains and oxide film on the surface;
[0041] Step (2) In the electrolyte mixture prepared in Example 1, the substrate is placed in a three-electrode system at a current density of 1 mA·cm -2 Electropolymerization was performed for 25 min under the conditions of , and then dried at room temperature for 12 h to obtain a nanoparticle pyrrole coated bipolar plate;
[0042] Step (3) ultrasonically dispersing 0.022 g of Ti3C2Tx and 0.068 g of the intercalated layered double hydroxide prepared in Example 2 in 150 mL of water respectively to obtain a Ti3C2Tx dispersion and an intercalated layered double hydroxide dispersion, then adding the Ti3C2Tx dispersion to the intercalated layered double hydroxide dispersion, and ultrasonically treating for 30 min to obtain a hybrid material dispersion;
[0043] Step (4) adding 3 g of glacial acetic acid to 150 mL of water and stirring for 15 min to obtain active water; adding 90 g of epoxy resin to 150 mL of water and stirring for 30 min to obtain diluted epoxy resin; adding the diluted epoxy resin to the active water, stirring for 1 h, and then standing for 24 h to obtain activated epoxy resin;
[0044] Step (5) adding the hybrid material dispersion prepared in step (3) to the activated epoxy resin prepared in step (4), stirring at a speed of 500 rpm for 1 hour, applying a 150 V DC voltage between the cathode nanoparticle pyrrole coated bipolar plate and the anode graphite plate for 2 minutes to complete the electrophoretic deposition process, and then baking at 170° C. for 20 minutes to obtain a conductive stable coating for the metal bipolar plate.
[0045] The three-electrode system is composed of a substrate as a working electrode, Ag / AgCl (sat.KCl) as a reference electrode, and a Pt sheet as a counter electrode.
[0046] Example 4
[0047] See also Figure 1 As shown, this embodiment discloses a method for preparing a conductive stable coating for a metal bipolar plate, comprising the following steps:
[0048] Step (1) cleaning the surface of the substrate to remove oil stains and oxide film on the surface;
[0049] Step (2) In the electrolyte mixture prepared in Example 1, the substrate is placed in a three-electrode system at a current density of 1 mA·cm -2 Electropolymerization was performed for 20 min under the conditions of , and then dried at room temperature for 16 h to obtain a nanoparticle pyrrole coated bipolar plate;
[0050] Step (3) ultrasonically dispersing 0.015 g of Ti3C2Tx and 0.09 g of the intercalated layered double hydroxide prepared in Example 2 in 100 mL of water respectively to obtain a Ti3C2Tx dispersion and an intercalated layered double hydroxide dispersion, then adding the Ti3C2Tx dispersion to the intercalated layered double hydroxide dispersion, and ultrasonically treating for 20 min to obtain a hybrid material dispersion;
[0051] Step (4) adding 4 g of glacial acetic acid to 100 mL of water and stirring for 20 min to obtain active water; adding 60 g of epoxy resin to 200 mL of water and stirring for 20 min to obtain diluted epoxy resin; adding the diluted epoxy resin to the active water, stirring for 1.5 h, and then standing for 12 h to obtain activated epoxy resin;
[0052] Step (5) adding the hybrid material dispersion prepared in step (3) to the activated epoxy resin prepared in step (4), stirring at a speed of 600 rpm for 0.5 h, applying a 160 V DC voltage between the cathode nanoparticle pyrrole coated bipolar plate and the anode graphite plate for 1 min to complete the electrophoretic deposition process, and then baking at 180° C. for 15 min to obtain a conductive stable coating for the metal bipolar plate.
[0053] The three-electrode system is composed of a substrate as a working electrode, Ag / AgCl (sat.KCl) as a reference electrode, and a Pt sheet as a counter electrode.
[0054] Example 5
[0055] See also Figure 1 As shown, this embodiment discloses a method for preparing a conductive stable coating for a metal bipolar plate, comprising the following steps:
[0056] Step (1) cleaning the surface of the substrate to remove oil stains and oxide film on the surface;
[0057] Step (2) In the electrolyte mixture prepared in Example 1, the substrate is placed in a three-electrode system at a current density of 1 mA·cm -2 Electropolymerization was performed for 30 min under the conditions of , and then dried at room temperature for 8 h to obtain a nanoparticle pyrrole coated bipolar plate;
[0058] Step (3) 0.03 g of Ti3C2Tx and 0.045 g of the intercalated layered double hydroxide prepared in Example 2 are ultrasonically dispersed in 200 mL of water to obtain a Ti3C2Tx dispersion and an intercalated layered double hydroxide dispersion, and then the Ti3C2Tx dispersion is added to the intercalated layered double hydroxide dispersion, and ultrasonically treated for 40 min to obtain a hybrid material dispersion;
[0059] Step (4) adding 2 g of glacial acetic acid to 200 mL of water and stirring for 10 min to obtain active water; adding 120 g of epoxy resin to 100 mL of water and stirring for 40 min to obtain diluted epoxy resin; adding the diluted epoxy resin to the active water, stirring for 0.5 h, and then standing for 36 h to obtain activated epoxy resin;
[0060] Step (5) adding the hybrid material dispersion prepared in step (3) to the activated epoxy resin prepared in step (4), stirring at a speed of 400 rpm for 1.5 hours, applying a 140 V DC voltage between the cathode nanoparticle pyrrole coated bipolar plate and the anode graphite plate for 3 minutes to complete the electrophoretic deposition process, and then baking at 160° C. for 25 minutes to obtain a conductive stable coating for the metal bipolar plate.
[0061] The three-electrode system is composed of a substrate as a working electrode, Ag / AgCl (sat.KCl) as a reference electrode, and a Pt sheet as a counter electrode.
[0062] Example 6
[0063] See also Figure 1 As shown, this embodiment discloses a method for preparing a conductive stable coating for a metal bipolar plate, comprising the following steps:
[0064] Step (1) cleaning the surface of the substrate to remove oil stains and oxide film on the surface;
[0065] Step (2) In the electrolyte mixture prepared in Example 1, the substrate is placed in a three-electrode system at a current density of 1 mA·cm -2 Electropolymerization was performed for 22 min under the conditions of , and then dried at room temperature for 14 h to obtain a nanoparticle pyrrole coated bipolar plate;
[0066] Step (3) ultrasonically dispersing 0.018 g of Ti3C2Tx and 0.08 g of the intercalated layered double hydroxide prepared in Example 2 in 130 mL of water respectively to obtain a Ti3C2Tx dispersion and an intercalated layered double hydroxide dispersion, then adding the Ti3C2Tx dispersion to the intercalated layered double hydroxide dispersion, and ultrasonically treating for 35 min to obtain a hybrid material dispersion;
[0067] Step (4) adding 2.5 g of glacial acetic acid to 170 mL of water and stirring for 12 min to obtain active water; adding 110 g of epoxy resin to 120 mL of water and stirring for 35 min to obtain diluted epoxy resin; adding the diluted epoxy resin to the active water, stirring for 0.7 h, and then standing for 30 h to obtain activated epoxy resin;
[0068] Step (5) adding the hybrid material dispersion prepared in step (3) to the activated epoxy resin prepared in step (4), stirring at a speed of 450 rpm for 1.2 hours, applying a 145 V DC voltage between the cathode nanoparticle pyrrole coated bipolar plate and the anode graphite plate for 2 minutes to complete the electrophoretic deposition process, and then baking at 165° C. for 22 minutes to obtain a conductive stable coating for the metal bipolar plate.
[0069] The three-electrode system is composed of a substrate as a working electrode, Ag / AgCl (sat.KCl) as a reference electrode, and a Pt sheet as a counter electrode.
[0070] Example 7
[0071] See also Figure 1 As shown, this embodiment discloses a method for preparing a conductive stable coating for a metal bipolar plate, comprising the following steps:
[0072] Step (1) cleaning the surface of the substrate to remove oil stains and oxide film on the surface;
[0073] Step (2) In the electrolyte mixture prepared in Example 1, the substrate is placed in a three-electrode system at a current density of 1 mA·cm -2 Electropolymerization was performed for 27 min under the conditions of , and then dried at room temperature for 10 h to obtain a nanoparticle pyrrole coated bipolar plate;
[0074] Step (3) ultrasonically dispersing 0.025 g of Ti3C2Tx and 0.055 g of the intercalated layered double hydroxide prepared in Example 2 in 180 mL of water respectively to obtain a Ti3C2Tx dispersion and an intercalated layered double hydroxide dispersion, then adding the Ti3C2Tx dispersion to the intercalated layered double hydroxide dispersion, and ultrasonically treating for 25 min to obtain a hybrid material dispersion;
[0075] Step (4) adding 3.5 g of glacial acetic acid to 120 mL of water and stirring for 18 min to obtain active water; adding 80 g of epoxy resin to 180 mL of water and stirring for 25 min to obtain diluted epoxy resin; adding the diluted epoxy resin to the active water, stirring for 1.2 h, and then standing for 15 h to obtain activated epoxy resin;
[0076] Step (5) adding the hybrid material dispersion prepared in step (3) to the activated epoxy resin prepared in step (4), stirring at a speed of 550 rpm for 0.8 h, applying a 155 V DC voltage between the cathode nanoparticle pyrrole coated bipolar plate and the anode graphite plate for 2 min to complete the electrophoretic deposition process, and then baking at 175° C. for 18 min to obtain a conductive stable coating for the metal bipolar plate.
[0077] The three-electrode system is composed of a substrate as a working electrode, Ag / AgCl (sat.KCl) as a reference electrode, and a Pt sheet as a counter electrode.
[0078] Comparative Example 1
[0079] Compared with Example 3, in Comparative Example 1, TiN was not added during the preparation of the conductive stable coating for the metal bipolar plate, that is, the bipolar plate obtained in step (1) was a polypyrrole coated bipolar plate, and other conditions remained unchanged.
[0080] Comparative Example 2
[0081] Compared with Example 3, in Comparative Example 2, in the process of preparing the conductive stable coating for the metal bipolar plate, no intercalated layered double hydroxide was added, that is, the Ti3C2Tx dispersion was obtained in step (2), and other conditions remained unchanged.
[0082] Comparative Example 3
[0083] Compared with Example 3, in the process of preparing the conductive stable coating for metal bipolar plates in Comparative Example 3, no hybrid material dispersion liquid is used, that is, the conductive stable coating for metal bipolar plates obtained in step (2) is unchanged, and other conditions remain unchanged.
[0084] Experimental example
[0085] The performance of the conductive stable coatings for metal bipolar plates prepared in Examples 3-7 and Comparative Examples 1-3 was tested:
[0086] 1. Corrosion resistance test
[0087] The corrosion resistance of the bipolar plate coatings prepared in Examples 3-7 and Comparative Examples 1-3 was measured using a three-electrode electrochemical test system. The solution was 0.5M H2SO4+5ppm HF solution, the solution temperature was 80°C, and the standard operating voltage was 0.6V. The measurement results are shown in Table 1:
[0088] Table 1
[0089]
[0090] It can be seen from Table 1 that the corrosion current density of the bipolar plate coating prepared in Examples 3-7 at a standard working voltage of 0.6 V is 1×10 -6 A / cm2 decreased by about 2 orders of magnitude, and has good corrosion resistance; from the comparison between comparative example 1 and embodiment 3, it can be seen that in the process of preparing the conductive stable coating for metal bipolar plates of the present invention, adding TiN can improve the corrosion resistance of the coating; from the comparison between comparative example 2 and embodiment 3, it can be seen that in the process of preparing the conductive stable coating for metal bipolar plates of the present invention, adding intercalated layered double hydroxide can improve the corrosion resistance of the coating; from the comparison between comparative example 3 and embodiment 3, it can be seen that in the process of preparing the conductive stable coating for metal bipolar plates of the present invention, using a hybrid material dispersion can improve the corrosion resistance of the coating.
[0091] 2. Contact resistance test
[0092] An assembly preload of 1.5 MPa was applied to the surface of the bipolar plate coating prepared in Examples 3-7 and Comparative Examples 1-3, and a contact resistance test and a contact resistance test after corrosion for 24 hours were performed. The results are shown in Table 2.
[0093] Table 2
[0094]
[0095] It can be seen from Table 2 that the contact resistance of the bipolar plate coating prepared in Examples 3-7 as deposited is and the contact resistance after 24 hours of corrosion meets the requirements of the U.S. Department of Energy standard of less than 10 mΩ·cm 2 , having good electrical conductivity and corrosion resistance; from the comparison of comparative example 1 and example 3, it can be seen that in the process of preparing the conductive stable coating for metal bipolar plates of the present invention, adding TiN can improve the conductivity and corrosion resistance of the coating; from the comparison of comparative example 2 and example 3, it can be seen that in the process of preparing the conductive stable coating for metal bipolar plates of the present invention, adding intercalated layered double hydroxide can improve the conductivity and corrosion resistance of the coating; from the comparison of comparative example 3 and example 3, it can be seen that in the process of preparing the conductive stable coating for metal bipolar plates of the present invention, using a hybrid material dispersion can improve the conductivity and corrosion resistance of the coating.
[0096] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0097] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a conductive stable coating for a metal bipolar plate, characterized in that: The following steps are involved: Step (1) cleaning the surface of the substrate to remove oil stains and oxide film on the surface; Step (2) electropolymerizing in an electrolyte mixture using a three-electrode system under constant current conditions, and drying to obtain a nanoparticle pyrrole coated bipolar plate; Step (3) ultrasonically dispersing Ti3C2Tx and intercalated layered double hydroxide in water respectively to obtain a Ti3C2Tx dispersion and an intercalated layered double hydroxide dispersion, then adding the Ti3C2Tx dispersion to the intercalated layered double hydroxide dispersion, and after ultrasonic treatment, obtaining a hybrid material dispersion; Step (4) adding the diluted epoxy resin into the activated water, stirring and then standing to obtain the activated epoxy resin; Step (5) adding the hybrid material dispersion prepared in step (3) to the activated epoxy resin prepared in step (4), stirring, applying voltage between the cathode nanoparticle pyrrole coated bipolar plate and the anode graphite plate, completing the electrophoretic deposition process, and baking to obtain a conductive stable coating for the metal bipolar plate; The method for preparing the electrolyte mixture comprises the following steps: 0.1-0.2 g of TiN nanoparticles and 0.14-0.28 g of camphorsulfonic acid are added to 1-2 L of water, and after ultrasonic treatment for 20-40 min, nitrogen is passed through for 20-40 min, and then 7.9-16 g of pyrrole and 6.6-13.1 g of phytic acid are added to obtain an electrolyte mixture; The preparation method of the intercalated layered double hydroxide comprises the following steps: 6.1-12.2 g of MgCl2·6H2O and 5.6-11.2 g of Al(NO3)3·9H2O are dissolved in 100-200 mL of water to obtain a mixed solution A, and then 7.3-15 g of Na2MoO4·2H2O and 5.4-10.8 g of urea are dissolved in 100-200 mL of water to obtain a mixed solution B. The mixed solution A and the mixed solution B are mixed, and the pH is adjusted to 9-10 with a 1 mol / L NaOH solution, and then stirred at 80-100° C. for 4-6 h in a nitrogen atmosphere, reacted in a hydrothermal reactor at 110-130° C. for 24-48 h, filtered, and the filter residue is washed with deionized water 3-5 times, and freeze-dried to obtain an intercalated layered double hydroxide.
2. The method for preparing a conductive stable coating for a metal bipolar plate according to claim 1, characterized in that: The substrate in step (1) is a steel bipolar plate for a fuel cell.
3. The method for preparing a conductive stable coating for a metal bipolar plate according to claim 1, characterized in that: In step (2), the current density of the constant current is 1 mA cm -2 ; The electropolymerization time is 20-30min; Drying conditions: The drying temperature is room temperature, and the drying time is 8-16h; The three-electrode system consists of a substrate as a working electrode, Ag / AgCl (sat.KCl) as a reference electrode, and a Pt sheet as a counter electrode.
4. The method for preparing a conductive stable coating for a metal bipolar plate according to claim 1, characterized in that: In the step (3), the dosage ratio of Ti3C2Tx, layered double hydroxide and water is (0.015-0.03) g: (0.045-0.09) g: (100-200) mL; and the ultrasonic treatment time is 20-40 min.
5. The method for preparing a conductive stable coating for a metal bipolar plate according to claim 1, characterized in that: In the step (4), the active water is obtained by adding 2-4 g of glacial acetic acid into 100-200 mL of water and stirring for 10-20 min; the diluted epoxy resin is obtained by adding 60-120 g of epoxy resin into 100-200 mL of water and stirring for 20-40 min; the stirring treatment time is 0.5-1.5 h; and the standing time is 12-36 h.
6. The method for preparing a conductive stable coating for a metal bipolar plate according to claim 1, characterized in that: In the step (5), the stirring treatment conditions are: the stirring treatment time is 0.5-1.5h, and the stirring treatment speed is 400-600rpm; the voltage application method is: applying a 140-160V DC voltage for 1-3min; and the baking conditions are: the baking temperature is 160-180°C, and the baking time is 15-25min.
7. A conductive stable coating for a metal bipolar plate prepared by the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Bipolar plate for electrochemical cells and method for the production thereof
CN107210456A
Preparation method of Ti3SiC2 ceramic coating on metal bipolar plate and metal bipolar plate
CN114561680A